If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39 + 0.75x = x Solving 39 + 0.75x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 39 + 0.75x + -1x = x + -1x Combine like terms: 0.75x + -1x = -0.25x 39 + -0.25x = x + -1x Combine like terms: x + -1x = 0 39 + -0.25x = 0 Add '-39' to each side of the equation. 39 + -39 + -0.25x = 0 + -39 Combine like terms: 39 + -39 = 0 0 + -0.25x = 0 + -39 -0.25x = 0 + -39 Combine like terms: 0 + -39 = -39 -0.25x = -39 Divide each side by '-0.25'. x = 156 Simplifying x = 156
| (4z+2)+(5z-3)= | | T*4-3=12 | | 5x^2+10x+46=0 | | 14=-0.5x^2+46 | | 3(4x-1)=9x+6 | | 18x-6=20x-12 | | A*5+6=10 | | -30de+12=18d | | 5t+6-2r=7r-10 | | y+9x^3y=0 | | 4x+1=4x-2 | | 3x-5x+3=x-7+10 | | -5(x+2)+3x=-5(x-3)+3x | | 70x^3+112x-1=0 | | 108=-6(x-8)-4x | | 7n=50+24 | | Y-3=-(x-5) | | (5x+y)+(2x+6y)= | | 2(x+9)=26 | | 3*8x=1.5e^2x | | x^4+0.5x^3-6x^2+5=0 | | g-(-7)=13 | | 33=6a+2 | | 20p-(7+2p)= | | z^2+(4+2i)z+(2-3i)=0 | | 39-15y=-31-5y | | 21y^14-7y^4=0 | | 2y-4x=-3-2x+y | | 8x-5=63 | | (3.2+1)-(0.6*7)= | | Logx(256)=2 | | 5+2y=(-1) |